Possibilidades e limites vivenciados por uma professora em sua primeira experiência com modelagem na educação matemática - Alessandra Cristina da Silva (2012)
This study tried to comprehend the possibilities and limits experienced by a mathematics teacher in her first experience with modeling in mathematics education. This search was realized with a mathematics teacher that teaches in a professionalizing high school of Belo Horizonte. The work was developed in a first grade class. The empirical part of the search was marked by four moments: class observations; planning of activity that promotes the implementation of modeling in mathematics; the implementation of the activity; interview realized with the teacher, in the end of each meeting, when she reported her impressions about the work with modeling. The methodological approach is qualitative and the data collection was made through participants observation (SPRAFLEY, 1980; FLICK, 2009), semi- structured interview (ALVES MAZZOTTI, 1998) and notes. The mathematic modeling in mathematics education was considered as an environment of learning (BARBOSA, 2001) that goes over the method that can be used in the mathematics learning because of the interdisciplinary form and maintaining dialogue with reality problems. In this search, the approach adopted about the teachers training is the continuing education that begins from the teaching practice, in order to move toward possible solutions close to the school reality (FIORENTINI; NACARATO, 2005). The analysis of the data was realized by the way of three categories that point out the relation of the teacher with the time (TEIXEIRA, 2006), the characteristic of unpredictability of work with modeling and the factors that favored the work with modeling. The results of the search showed that the relation with time and the unpredictability create moments of stress, but it does not configured in limits, because the positive evaluation of the teacher experience, that wants to do future experiences with modeling. The possibilities of the work with modeling were favored by the prospect of mathematics investigations of teacher job.